Pengembangan Sensor dan Aktuator Dasar Berbasis Arduino pada Capaian Pembelajaran Embedded System Fase F - Syamsul Jamal; Sulis Janu Hartati; Abdul Wahid (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The objectives of research on the development of basic Arduino-based sensors and actuators on the learning outcomes of embedded systems phase f are: able to develop learning media in embedded system learning outcomes, able to carry out learning media activities with embedded system learning outcomes, can improve embedded system learning outcomes for class XI students in the field of industrial electronics engineering expertise at SMK Negeri 1 Tambelangan. This study adopted a research and development methodology consisting of; opportunities and challenges, data collection, product design, design verification, design revision, product test, product revision, usage test, and product revision. The object of this research is sensor and actuator basic learning media. Data collection was carried out by direct observation and filling out a questionnaire (questionnaire). The validation of learning media was carried out by two material experts and two media experts, while the trial use was carried out at SMK Negeri 1 Tambelangan. The data analysis technique used in this research is quantitative descriptive analysis. The results of the validation of the material from this research reached an eligibility of 90% and the results of the validation of the media from this study showed an eligibility of 89.98% while for user trials it obtained 80% with a very feasible category. The use of learning media sensor and actuator trainers can increase the percentage of students passing from Pretest by 6% to PostTest to 80.0%.